LANGUAGE COMPARISON OF PRE & POST INDEPENDENCE INDIAN ENGLISH FICTION (International Journal of Food and Nutritional Sciences, 2022)
This particular periodical places a major emphasis on the language of English literature inIndia prior & post to the country's independence, which is seen as being of critical importance.Additionally, it embraces all facets of literary freedom in a thorough manner